No evidence for association between rs10191329 severity locus and longitudinal disease severity in 1813 relapse-onset multiple sclerosis patients from the MSBase registry - Campagna, Maria Pia; Havrdova, Eva Kubala; Horakova, Dana; Izquierdo, Guillermo; Matesanz, Fuencisla; Eichau, Sara; Lechner-Scott, Jeannette; Taylor, Bruce V; García-Sanchéz, Maria-Isabel; Alcina, Antonio; van der Walt, Anneke; Butzkueven, Helmut; et al. (Multiple sclerosis (Houndmills, Basingstoke, England), 2024)
BACKGROUND: The International Multiple Sclerosis Genetics Consortium and MultipleMS Consortium recently reported a genetic variant associated with multiple sclerosis (MS) severity. However, it remains unclear if these variants remain associated with more robust, longitudinal measures of disease severity. METHODS: We examined the top variant, rs10191329, from Harroud et al.'s study in 1813 relapse-onset MS patients from the MSBase Registry to assess association with longitudinal disease severity. RESULTS: Our analysis revealed no significant association between rs10191329 genotype and longitudinal binary disease severity (p > 0.05). CONCLUSION: These findings highlight the complexity of genetic factors mediating long-term MS outcomes and the need for further research.
Keywords: dospělí; Genotype; Female; disease severity; Adult; ženské pohlaví; jednonukleotidový polymorfismus; longitudinální studie; Registries; relabující-remitující roztroušená skleróza; genetics; lidé; Multiple Sclerosis; Polymorphism, Single Nucleotide; genotyp; roztroušená skleróza; stupeň závažnosti nemoci; Male; Multiple Sclerosis, Relapsing-Remitting; lidé středního věku; registrace; mužské pohlaví; Severity of Illness Index; Multiple sclerosis; Middle Aged; Longitudinal Studies; Humans